2021
DOI: 10.1111/jre.12923
|View full text |Cite
|
Sign up to set email alerts
|

Interruption of regular dental visits during the COVID‐19 pandemic due to concerns regarding dental visits was associated with periodontitis in Japanese office workers

Abstract: Objective To investigate the interrelationships among concerns regarding dental visits, the status of regular dental visits, and periodontal health during the coronavirus disease 2019 (COVID‐19) pandemic. Background Continuous oral health care and regular dental visits are important for maintaining periodontal health. Due to the possibility of contracting COVID‐19, individuals have been reluctant to visit medical institutions. It is unclear how the periodontal health of the Japanese population has been affecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 19 publications
(34 reference statements)
0
20
0
1
Order By: Relevance
“…Previous studies have shown that since the beginning of the COVID-19 pandemic, RDCs have been postponed due to factors related to dental practices and patients [ 14 , 15 , 16 , 17 , 18 , 19 ]; these studies were conducted in the early stages of the pandemic. RDCs were postponed because of their low urgency among dental treatments [ 17 , 18 , 19 ], and many people feared dental visits due to the pandemic [ 28 , 29 , 30 , 31 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Previous studies have shown that since the beginning of the COVID-19 pandemic, RDCs have been postponed due to factors related to dental practices and patients [ 14 , 15 , 16 , 17 , 18 , 19 ]; these studies were conducted in the early stages of the pandemic. RDCs were postponed because of their low urgency among dental treatments [ 17 , 18 , 19 ], and many people feared dental visits due to the pandemic [ 28 , 29 , 30 , 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…A study in Germany conducted in July 2020 found that 22% postponed dental visits because of the COVID-19 pandemic, and of those who reported postponement, 72% reported postponing RDCs [15]. In November 2020, a survey of workers in a local municipal office in Japan showed that 28.7% of the respondents stopped RDCs due to the COVID-19 pandemic [16].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The reduced dental visits among the elderly may have been influenced by the fact that routine dental services were partially restricted when COVID-19 infection first began to spread, rather than by anxiety and stress factors. In the elderly prone to periodontal complications, interruption of home life and dental care due to COVID-19 may exacerbate periodontal disease [19]. Weber et al [20] reported that the decrease in dental-related quality of life of older adults requiring care during the COVID-19 pandemic was significantly associated with decreased social support.…”
Section: Discussionmentioning
confidence: 99%